A Novel Energy Efficient Clustering Algorithm for Wireless Sensor Networks - Singh, S. P.; Sharma, S. C. (Engineering, Technology & Applied Science Research, 2017)
Wireless sensor networks (WSNs) are composed of huge amount of tiny resource constrained devices known as sensors. The demand for an energy efficient structure is becoming gradually more essential in WSNs. Energy efficient clustering is a distinguished optimization problem which has been studied extensively to expand the life span of WSNs. In this manuscript, a new energy efficient clustering scheme for WSNs with the use of Particle Swarm Optimization (PSO) is proposed. The clustering algorithm is implemented with the goal of concurrently minimizing the intra-cluster distance along with optimizing the usage of network energy. The presented algorithm is tested widely and results are analyzed and compared with previous ones to show the supremacy in term of alive nodes, energy consumption, packet delivery ratio, and system throughput. Simulation results show that the proposed algorithm outperforms other existing algorithms.